Pancreatic Hydatid Cyst Causing Acute Pancreatitis: A Case Report and Literature Review - Bayan Alsaid; Maryam Alhimyar; Fadi Rayya (Case Reports in Surgery)
Hydatidosis is a public health problem in endemic countries. Hydatid cysts are located usually in the liver and the lungs. Primary pancreatic hydatid cyst is in unusual location and rarely causes acute pancreatitis. In this paper, we report a case of a 34-year-old man who admitted with recurrent acute pancreatitis. Following the preoperation investigations, the primary impression was a pancreatic pseudocyst. During surgery, a primary hydatid cyst was detected in the pancreas measuring 35 × 20 × 15 cm. The treatment consisted of evacuation and external draining of the cyst. In addition, we summarized 14 cases of primary hydatid cyst of the pancreas associated with acute pancreatitis reported in the literature.